End of life in acute hospital setting—A systematic review of families' experience of spiritual care. Issue 7 (3rd February 2020) - Hennessy, Nora; Neenan, Kathleen; Brady, Vivienne; Sullivan, Melissa; Eustace-Cooke, Jessica; Timmins, Fiona
Abstract: Aims and objectives: To systematically review qualitative studies exploring families' experiences of spiritual care at the end of life in acute hospital settings. Background: Although there is a widespread belief that the consideration of spiritual and religious needs is outdated in the context of secularism, from a practical perspective patients and families appear to benefit from spiritual support at the end of life. Methods: Six key databases, CINAHL, MEDLINE, EMBASE, Global Health Library, Web of Science and Applied Social Sciences Index and Abstracts (ASSIA), were searched, and three reviewers independently extracted the data and coded them into themes and subthemes. The Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) was used as a reporting framework. Results: Five main themes emerged: anticipating needs; honouring the family by honouring the patient; personal connection; lack of sensitivity; and making space for religious and spiritual practices. Conclusions: Families experiencing end‐of‐life care in acute hospital settings may benefit from spiritual care. While this can also be considered as fundamental care, understanding this through the lenses of spiritual care allows for incorporation of religious and spiritual practices that many seek at this time, irrespective of their faith perspectives. Relevance to clinical practice: Although hospice care is well established internationally, many families experience end‐of‐life care in acute hospital settings. Nurses usually get to know families well during this time; however, the demands of the clinical environment place restrictions on family care and perceptions of lack of communication, limited support and/or limited sensitivity can compound families' suffering. Consideration of families' spiritual needs can help to support families during this time. Nurses are ideally placed for this and can anticipate and plan for patient and family needs in this regard, or refer to a specialist, such as the Healthcare Chaplain.